Information security theory and practice security and privacy of mobile devices in wireless communication : 5th IFIP WG 11.2 International Workshop, WISTP 2011, Heraklion, Crete, Greece, June 1-3, 2011 : Proceedings - WISTP 2011 (2011 Erakleion, Greece); Ardagna, Claudio A.; Zhou, Jianying; SpringerLink (Online service). (Berlin Springer, 2011)
This volume constitutes the refereed proceedings of the 5th IFIP WG 11.2 International Workshop on Information Security Theory and Practices: Security and Privacy of Mobile Devices in Wireless Communication, WISTP 2011, held in Heraklion, Crete, Greece, in June 2011. The 19 revised full papers and 8 short papers presented together with a keynote speech were carefully reviewed and selected from 80 submissions. They are organized in topical sections on mobile authentication and access control, lightweight authentication, algorithms, hardware implementation, security and cryptography, security attacks and measures, security attacks, security and trust, and mobile application security and privacy.
Electronic reproduction.
Keywords: Mobile communication systems -- Security measures -- Congresses; Data protection -- Congresses; Computer systems -- Access control -- Congresses; Smart cards -- Congresses; Electronic books